CURRENT STATUS AND ACHIEVEMENTS OF THE MODULE 'PHYSICAL BASIS OF LIFE ACTIVITIES AND APPLICATIONS IN MEDICINE' IN THE MEDICAL DOCTOR TRAINING PROGRAM OF HANOI MEDICAL UNIVERSITY (Vietnam Journal of Community Medicine, 2026)
Module S1.4: “The Physical Basis of Life Activities and its Applications in Medicine” was designed to be taught during Phase I of the revamped Medical Doctor (MD) training program at Hanoi Medical University. Based on an analysis of the advantages and difficulties in teaching and learning, we introduced and implemented practical solutions to address these challenges. Over the five years of deployment, Module S1.4 has received positive feedback, with evaluation scores exceeding 75% across all aspects—including curriculum content, teaching methodology, and assessment methods—from both the faculty and the MD students. The module's assessment results demonstrate the program's stability, alignment with training objectives, and suitability for the required learning outcomes. The increasing percentage of students achieving good and excellent grades over the years highlights the effectiveness of diverse teaching and learning methods. Furthermore, the module's faculty team has consistently been recognized and appreciated by students year after year for their enthusiasm, dedication, and passion, which serves as further proof of the success of Module S1.4. Based on these research findings, we are finalizing a high-quality module curriculum that meets the MD output standards, thereby contributing to the enhancement of student competency and the promotion of international integration.
Keywords: Module S1.4, competency, advantages, challenges and solutions, feedback.